Power conversion of renewable energy systems - Fuchs, Ewald F. (Springer, 2011)
Power Conversion of Renewable Energy Systems introduces conventional energy conversion components and systems, as well as those related to renewable energy which are important for a smart grid design.  This volume covers systems first, and then in subsequent chapters describes the components of energy systems in detail.  Readers will find examples of renewable and conventional energy and power systems, including energy conversion, variable-speed drives and power electronics, in addition to magnetic devices such as transformers and rotating machines.  Applications of PSpice, MATLAB, and Mathematica software are employed along with solutions to over 168 application examples.  Notable firsts  include: calculated detailed flux distributions of magnetic components, which enhance their understanding ; compensation of  intermittently operating renewable source outputs by short-term and long-term electrical storage plants to maintain frequency/load control of a smart grid  Power Conversion of Renewable Energy Systems aims to instruct readers how to actively apply the theories discussed within.  It would be ideal for researchers, undergraduate and graduate students, and engineers working with energy systems and renewable energy.  Instructor manual will be available upon request.